(untitled) (International journal of artificial intelligence, 2025)
This article presents research conducted by scientists on the history of the Karakalpaks of the Zarafshan oasis from the second half of the 20th century to the beginning of the 21st century. However, there are few separate studies on the entry of the Karakalpak tribes into the Zarafshan oasis, their settlement, and their adaptation to the socio-political life of the oasis. The study of the participation of the Karakalpak people, who by fate made the oasis their homeland, in ethno-integration processes based on new historical and ethnographic data still retains its scientific and practical significance today. We tried to write the article taking into account the urgent task of studying and analyzing the available sources and shedding light on the history of the oasis Karakalpaks.